2018
DOI: 10.3389/fneur.2017.00723
|View full text |Cite
|
Sign up to set email alerts
|

Action Observation Plus Sonification. A Novel Therapeutic Protocol for Parkinson’s Patient with Freezing of Gait

Abstract: Freezing of gait (FoG) is a disabling symptom associated with falls, with little or no responsiveness to pharmacological treatment. Current protocols used for rehabilitation are based on the use of external sensory cues. However, cued strategies might generate an important dependence on the environment. Teaching motor strategies without cues [i.e., action observation (AO) plus Sonification] could represent an alternative/innovative approach to rehabilitation that matters most on appropriate allocation of atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
142
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(145 citation statements)
references
References 57 publications
(71 reference statements)
1
142
0
2
Order By: Relevance
“…Moreover, changes in movement patterns associated with subliminal changes in frequency can also have practical implications. For instance, enhancement in breathing (Murgia et al, 2016 ), music learning (Hol, 2011 ; Lahav et al, 2013 ), arm reaching (Maulucci and Eckhouse, 2001 ; Schmitz et al, 2014 ; Scholz et al, 2016 ), gait (Maulucci and Eckhouse, 2011 ; Zhang et al, 2013 ; Mezzarobba et al, 2017 ), sports (Eriksson and Bresin, 2010 ; Sigrist et al, 2013 ), performance with real-time auditory feedback has been demonstrated in a few studies. Here, subliminal modulation in frequency during training can be introduced to enhance variability in movement patterns, which further can lead to a dynamic learning pattern (Stein et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, changes in movement patterns associated with subliminal changes in frequency can also have practical implications. For instance, enhancement in breathing (Murgia et al, 2016 ), music learning (Hol, 2011 ; Lahav et al, 2013 ), arm reaching (Maulucci and Eckhouse, 2001 ; Schmitz et al, 2014 ; Scholz et al, 2016 ), gait (Maulucci and Eckhouse, 2011 ; Zhang et al, 2013 ; Mezzarobba et al, 2017 ), sports (Eriksson and Bresin, 2010 ; Sigrist et al, 2013 ), performance with real-time auditory feedback has been demonstrated in a few studies. Here, subliminal modulation in frequency during training can be introduced to enhance variability in movement patterns, which further can lead to a dynamic learning pattern (Stein et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The perception of additional real-time acoustic feedback driven by dynamic or kinematic movement parameters obviously supports sensory/perceptual-motor representations (Effenberg, 2005 ; Schmitz et al, 2013 ) by enhancing cross-modal stimulation (Scholz et al, 2015 ; Ghez et al, 2017 ), multisensory integration (Schmitz et al, 2013 ; Effenberg et al, 2016 ), internal motor simulation (Schmitz and Effenberg, 2017 ), and neural plasticity (Altenmüller et al, 2009 ; Ghai et al, 2017c ). Literature indicates strong associations between auditory and motor areas for enhancing the performance in music (Lahav et al, 2013 ), breathing (Murgia et al, 2016 ), writing (Effenberg et al, 2015 ; Danna and Velay, 2017 ), sports (Sigrist et al, 2013 , 2015 ; Effenberg et al, 2016 ), and rehabilitation (Altenmüller et al, 2009 ; Murgia et al, 2015 ; Pau et al, 2016 ; Scholz et al, 2016 ; Ghai et al, 2017c ; Mezzarobba et al, 2017 ). Strong auditory motor couplings have also been confirmed in neuroimaging studies, where enhanced activation in cortical and sub-cortical structures associated with biological motion perception were reported (Scheef et al, 2009 ; Schmitz et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies included participants with a disease duration of at least 5 years and without dementia (Mini-Mental Status Examination > 24). Four studies included patients with freezing of gait, with an incidence of at least one episode in a week and a duration of at least 2 s for each episode (17,(27)(28)(29). Finally, in addition to a PD control group, two studies provided a sample of healthy controls matched for age and sex with patients (18,27).…”
Section: Participantsmentioning
confidence: 99%
“…During observation, participants were asked to keep their attention on movement details without performing any kind of movement. Only one study, after observation of each video-clip, asked patients to imitate the observed actions while they were still watching the same video (28). Other four studies asked patients to imitate the observed tasks after observation (17,20,27,29), whereas the remaining two studies delivered AOT without imitation (18,19).…”
Section: Characteristics Of Aot Interventionsmentioning
confidence: 99%
“…Action observation has been proposed to provide an alternative and innovative approach to rehabilitation ( Mezzarobba et al, 2017 ; Scott et al, 2018 ), and a deeper understanding of the effects of body side, posture, and perspective is crucial for identifying the most effective conditions for stimulation of the motor system during action observation.…”
Section: Introductionmentioning
confidence: 99%